2021
DOI: 10.1515/med-2021-0322
|View full text |Cite
|
Sign up to set email alerts
|

Cell population data in identifying active tuberculosis and community-acquired pneumonia

Abstract: Objective Leukocyte morphological parameters known as CPD (cell population data) is detected by hematology analyzer UniCel DxH800 with VCS technology. This study aimed to investigate the diagnostic efficacy of morphological changes in CPD parameters in distinguishing active tuberculosis from community-acquired pneumonia. Methods From October 2018 to February 2019, 88 patients with active tuberculosis, 78 patients with communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The final model (risk factors including night sweats, hemoptysis, weight loss, tuberculosis exposure and upper lobe infiltrate) obtained an AUC of 0.89 (95%CI: 0.85—0.93), which was a better prediction model for pulmonary tuberculosis based on clinical information at present. In laboratory studies, Sun et al [ 22 ] used multiple parameters of cell population data used to characterize white blood cells morphology to identify APTB and CAP. Their results showed that neutrophil mean conductivity, monocyte mean volume and monocyte mean conductivity had high discrimination ability in identifying the two diseases, and AUC could reach 0.99 when used in combination.…”
Section: Discussionmentioning
confidence: 99%
“…The final model (risk factors including night sweats, hemoptysis, weight loss, tuberculosis exposure and upper lobe infiltrate) obtained an AUC of 0.89 (95%CI: 0.85—0.93), which was a better prediction model for pulmonary tuberculosis based on clinical information at present. In laboratory studies, Sun et al [ 22 ] used multiple parameters of cell population data used to characterize white blood cells morphology to identify APTB and CAP. Their results showed that neutrophil mean conductivity, monocyte mean volume and monocyte mean conductivity had high discrimination ability in identifying the two diseases, and AUC could reach 0.99 when used in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, multiple tools are available for the accurate diagnosis of PT or CAP [8][9][10] , however, the availability of these techniques in many places may be limited. The assessment of cell counts and the relationships between different types of blood cells has been proposed to provide useful and easily accessible information for distinguishing between these two conditions 9,11 . An elevated monocyte/lymphocyte ratio (MLR) has been suggested as an indicative marker of tuberculosis, while a low value may indicate bacterial pneumonia 12,13 .…”
Section: Introductionmentioning
confidence: 99%